Low Concentration of S100A8/9 Promotes Angiogenesis-Related Activity of Vascular Endothelial Cells: Bridges among Inflammation, Angiogenesis, and Tumorigenesis? - Changyou Li; Siyuan Li; Changkai Jia; Lingling Yang; Zicheng Song; Yiqiang Wang (Mediators of Inflammation)
Previous studies showed that several members of the S100A family are involved in neovascularization and tumor development. This study checked whether low concentrations of S100A8 or S100A9 has any effect on the behaviour of vascular endothelial cells. A human umbilical vascular endothelial cell (HUVEC) line was used to measure vascular endothelial cell bioactivity related to angiogenesis, such as cell proliferation, migration, and vessel formation. In the low concentration range up to 10 μg/mL, either each alone or in combination, S100A8 and S100A9 proteins promoted proliferation of HUVEC cells in a dose-dependent manner. The presence of both proteins in culture showed additive effects over each single protein. Both proteins enhanced HUVEC cells to migrate across the transwell membrane and to form tube-like structures on the Matrigel surface. When mixed in Matrigel and injected subcutaneously in Balb/c mice, both proteins increased vessel development in the gel plugs. Microarray assay of HUVEC cells treated with 10 μg/mL S100A8 revealed that ribosome pathway, pathogenic Escherichia coli infection pathway, apoptosis, and stress response genes were modulated by S100A8 treatment. We propose that S100A8 and S100A9 proteins from either infiltrating inflammatory cells or tumor cells play an important role in the interplay among inflammation, angiogenesis, and tumorigenesis.